Red Snapper Fish Supplier Analysis Based on Vendor Perfomance Indicator with Analytical Hierarchi Process - Mustaniroh, Siti Asmaul; Santoso, Sri Maryani; Oktora, Etyka Dwi (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
PT. Inti Luhur Fuja Abadi is one company that specializes in freezing fish. The role of suppliers to increase performance production is well known. This factory has some problems i.e. delivery delay of raw material, low fish quality, and bad response. Evaluation is needed to determine good performance of supply. Â The aim of this study is to evaluate the performance of suppliers based on VPI with AHP method. The performance evaluation conducted in 6 red snapper suppliers. The results showed that the suitability of raw material sensory quality to company quality standard and the ability to supply the red snapper with consistent quality had the greatest weight value of 34%. Other VPI showed the price of the suitability of suppliers to company standard of 13.44%, price fluctuation of 2.56%, time of the arrival of 5.85%, flexibility in delivery schedule of 0.72%, delivery accuracy of 2.43%, response to complaints of 5.88%, and response to demand changes of 1.12%. Supplier performance rating based on performance evaluations was respectively Supplier A (25.08%), Supplier C (21.3%), Supplier E (17.43%), Supplier B (15.06%), Supplier D (11.01%), and Supplier F (10.25%).Keywords: supplier, Vendor Performance Indicator, Analytical Hierarchy Process